Evaluation of adherence and knowledge retention for adrenaline autoinjector use in Hymenoptera venom-allergic patients with c-KIT p.D816V - Močnik, Tea (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Introduction: Severe anaphylaxis in patients with clonal mast cell disorders highlights the need for proper use of adrenaline autoinjectors. This study assessed knowledge retention and adherence to autoinjector use in c-KIT p.D816V-positive individuals with hymenoptera venom allergy undergoing venom immunotherapy (VIT) and prescribed two autoinjectors. Methods: Seventy-one VIT patients received personalized autoinjector education, with knowledge assessed at 3, 4 to 12, 12 to 24, and > 24 months. Fifteen patients 5 years post-VIT underwent video-based retraining and were assessed 1 month later. Results: Knowledge retention was 82.3% at 3 months, dropping to 40.0% at 12 to 24 months (p = 0.0160) and 22.2% after 24 months (p = 0.0005), indicating a clear decline over time. Common errors included ignoring the safety cap (16.7%), insufficient injection force, finger injection risk, and upper arm activation (totaling 19.0%). In addition, 19.8% failed to hold the autoinjector in the muscle for 3 seconds, 26.9% did not know to lie supine during anaphylaxis, and 14.3% did not seek emergency help. In the video-retrained group, 80.0% lacked proficiency 1 month later, 73.3% were unaware of the second dose, and 66.7% did not carry their devices. Conclusions: Ongoing tailored education is essential to ensure effective autoinjector use, especially in c-KIT p.D816V-positive venom-allergic patients. Video instruction alone may be insufficient.
Keywords: Anafilaksija; Anaphylaxis; autoinjector; avtoinjektor; Epinefrin; Epinephrine; Hymenoptera; izobraževanje bolnikov; kožekrilci; patient education; Samoaplikacija; Self-Administration